Collected stories - Henry, O., 1862-1910.; Horowitz, Paul J. (New Delhi : Gopsons Papers Ltd., 2000)
An illustrated collection of more than 200 stories arranged in chronological order of publication.
Keywords: Short stories; United States -- Social life and customs -- Fiction